2020
DOI: 10.1136/bcr-2020-238221
|View full text |Cite
|
Sign up to set email alerts
|

Influenza B associated acute necrotising encephalopathy with visual impairment in a child

Abstract: Influenza-associated encephalopathy/encephalitis (IAE) can result in serious neurological complications. We report a 4-year-old healthy female child with the diagnosis of IAE. Her clinical course was complicated by temporary visual impairment and significant motor deficits. Her unique ophthalmological findings have little precedent in previous literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The lesion was transient, which suggested that the virus's effect on the brain was reversible (Ventresca et al 2021). Another case was reported for a 4-year-old healthy female child who suffered from influenza-associated encephalopathy (IAE); the visualized symptoms included neurological complications of temporary visual impairment and significant motor deficits (Billa et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The lesion was transient, which suggested that the virus's effect on the brain was reversible (Ventresca et al 2021). Another case was reported for a 4-year-old healthy female child who suffered from influenza-associated encephalopathy (IAE); the visualized symptoms included neurological complications of temporary visual impairment and significant motor deficits (Billa et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The lesion was transient, which suggested that the virus's effect on the brain was reversible (Ventresca et al 2021). Another case was reported for a 4-year-old healthy female child who suffered from in uenza-associated encephalopathy (IAE); the visualized symptoms included neurological complications of temporary visual impairment and signi cant motor de cits (Billa et al 2020). However, the mechanism by which the in uenza virus could induce neuroin ammation is not fully understood.…”
Section: Introductionmentioning
confidence: 99%